2021
DOI: 10.1158/2159-8290.cd-20-1669
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2Extracellular Domain In-Frame Deletions Are Therapeutically Targetable Genomic Alterations That Function as Oncogenic Drivers in Cholangiocarcinoma

Abstract: We conducted next generation DNA sequencing on 335 biliary tract cancers and characterized the genomic landscape by anatomic site within the biliary tree. In addition to frequent FGFR2 fusions among patients with intrahepatic cholangiocarcinoma (IHCC), we identified FGFR2 extracellular domain in-frame deletions (EIDs) in 5 of 178 (2.8%) patients with IHCC, including two patients with FGFR2 p.H167_N173del. Expression of this FGFR2 EID in NIH3T3 cells resulted in constitutive FGFR2 activation, oncogenic transfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 67 publications
1
52
0
5
Order By: Relevance
“…The authors confirmed the importance of FRFR2 extracellular domain 'in-frame' deletions as oncogenic drivers in silico, in cell line models and in vivo and showed the ability of some FRGR inhibitors to block these activating signals. 7 Concerning clinical antitumor activity of FGFR inhibitors, partial responses were observed among these patients with FGFR2 extracellular domain in-frame deletions, comparing favorably with those reported for the different FGFR inhibitors in patients with IHCCs harboring FGFR2 fusions. These findings suggest that the degree of oncogenic addiction to FGFR2 may vary across these mutational contexts and support further clinical evaluation of FGFR inhibitors in patients with FGFR2 extracellular domain in-frame deletions.…”
Section: Targeting Fibroblast Growth Factor Receptor Beyond Fusions In Intrahepatic Cholangiocarcinoma: Fgfr2 Extracellular Domain In-frasupporting
confidence: 56%
“…The authors confirmed the importance of FRFR2 extracellular domain 'in-frame' deletions as oncogenic drivers in silico, in cell line models and in vivo and showed the ability of some FRGR inhibitors to block these activating signals. 7 Concerning clinical antitumor activity of FGFR inhibitors, partial responses were observed among these patients with FGFR2 extracellular domain in-frame deletions, comparing favorably with those reported for the different FGFR inhibitors in patients with IHCCs harboring FGFR2 fusions. These findings suggest that the degree of oncogenic addiction to FGFR2 may vary across these mutational contexts and support further clinical evaluation of FGFR inhibitors in patients with FGFR2 extracellular domain in-frame deletions.…”
Section: Targeting Fibroblast Growth Factor Receptor Beyond Fusions In Intrahepatic Cholangiocarcinoma: Fgfr2 Extracellular Domain In-frasupporting
confidence: 56%
“…For this purpose, futibatinib has shown promising results in patients who progressed after treatment with FGFR2 inhibitors. A further partial response has recently been observed in a patient treated with futibatinib who showed disease progression after developing an acquired L618F FGFR2 kinase domain mutation following a treatment with an oral FGFR-1/2/3 inhibitor (Debio 1347) [56].…”
Section: Tyrosine Kinase Receptorsmentioning
confidence: 95%
“…the constitutive activation of FGFR2 [25] , happening between the N-terminus containing exons 1-19 of FGFR2 with a functional tyrosine kinase domain and the C-terminus that contains the partner dimerisation domain. Recently, deletion-in-frame alteration has also been described in 2.8% of cases in a large series of 178 patients, also finding that this kind of alteration is targetable with FGFR inhibitors [26] .…”
Section: Molecular Characterization Of Biliary Tract Cancermentioning
confidence: 99%